PENGARUH INFLUENCER MARKETING BRAND IMAGE TERHADAP MINAT BELI TAS EIGER DI TIKTOK SHOP : STUDI KASUS PADA MAHASISWA UTM - Choiron Ramdhan; Triana Setiyarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of influencer marketing and brand image on the interest in buying Eiger bags at TikTok Shop, focusing on students at Trunojoyo University, Madura (UTM). The phenomenon of using TikTok as an e-commerce platform is increasing, especially among students who actively use social media. Influencer marketing is considered as one of the effective strategies in building brand image and encouraging consumer buying interest. The research method used is a quantitative approach with a descriptive and causal design. Data were obtained through a questionnaire based on a Likert scale of 1-5, which was distributed to 45 UTM student respondents selected using the proportional random sampling method. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, and multiple linear regression tests. The results showed that influencer marketing had a significant influence on the interest in buying Eiger bags at TikTok Shop, while brand image did not show a significant influence. Multiple linear regression tests revealed that the influencer marketing variable had a coefficient value of 0.721 with a p-value of 0.000, which indicated a positive and significant influence. On the other hand, the brand image variable has a coefficient of 0.182 with a p-value of 0.222, indicating that its effect on purchase intention is not significant. Simultaneously, influencer marketing and brand image collectively influence purchase intention, as evidenced by the significant F-test results. These findings provide important implications for digital marketing strategies, especially in maximizing the role of influencers to increase purchase intention. Businesses that want to increase sales through TikTok Shop are advised to further utilize the potential of credible influencers who have great influence among students. In addition, this study can contribute to the development of literature in the field of digital marketing and consumer behavior in the context of social media-based e-commerce.